Characteristics of Microplastics in Bivalves of Rock Oysters and Sea Clams in the South Central Coast, Vietnam - Thi Thom, Dang; Trung Ha, Dinh; Huong, Mai; Van Manh, Do (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Microplastics have emerged as one of the new substances causing environmental pollution, which is a growing concern because their nature can pose risks to human health and the environment. We analyzed characteristics of microplastics such as density, size, shape, and polymer types in natural rock oysters, Saccostrea sp , and sea clams Venus sp in the South Central Coast using Fourier Transform Infrared Spectroscopy (µFTIR) on a microscope Nicolet iN10 MX. The results showed that microplastics in Saccostrea sp and Venus sp present with density of 1 - 21 and 4 - 5 particles/individual, respectively. The average concentration of microplastics was about 0.25 - 1.59 particles/gram of fresh tissue weight. The size of microplastics ranged from 20 μm to more than 500 μm, mainly found in range of 50 - 150 μm. Commonly found microplastics shapes were fragment and fiber. There were ten polymer types found, of which the most common was polyethylene terephthalate (PET), accounting for 58%, and the popular nylon type with 10% of the total microplastics. In addition, some other polymers were also detected by FTIR technique, such as polypropylene (PP) contributing about 9% of the total microplastics, HDPE 30060M, and Melamine-urea-formaldehyde resin contributing 7%. In summary, this study investigated the presence of microplastics and assessed the risk of microplastics in bivalves that possibly affect human health (PHI index of 100.81).